Behavioral profiling in children and adolescents with Malan syndrome - Alfieri, Paolo; Montanaro, Federica Alice Maria; Macchiaiolo, Marina; Collotta, Martina; Caciolo, Cristina; Galassi, Paolo; Panfili, Filippo Maria; Cortellessa, Fabiana; Zollino, Marcella; Chinali, Marcello; Accadia, Maria; Seri, Marco; et al. (Frontiers in Child and Adolescent Psychiatry, 2023)
Malan syndrome (MALNS) is an ultra-rare genetic disorder caused by heterozygous chromosomal microdeletions involving the 19p13.2 region or loss-of-function variants in the NFIX gene. It is characterized by specific phenotypical features, intellectual disability (ID), and limitations in adaptive functioning and behavioral problems. In a previous work, we defined the cognitive, adaptive, linguistic and visuomotor ability profiles in a group of 15 MALNS individuals, providing quantitative data from standardized evaluations. Here, we further extend the characterization of MALNS by analyzing the behavioral and psychopathological comorbidities of the same cohort, administering standardized tests. Children were evaluated from October 2020 to January 2022. Retrospective data analysis was also performed. Assessment consisted of clinical observations, structured parent interviews, and parent-reported questionnaires. For each scale, comparisons between subtests were performed. Results of our analysis show that the most prevalent psychiatric comorbidities are represented by anxiety symptoms (including GAD, separation anxiety and specific phobias), ADHD, autistic symptoms, and social and attention problems. Of note, minimal or no signs of ASD were observed. In conclusion, our findings indicate that the psychopathological and behavioral comorbidities, together with cognitive impairment, language problems and sensory difficulties interfere with development, daily activities and social participation, therefore contributing to the severity of the disability associated with MALNS. Awareness of this profile by professionals and caregivers can promote prompt diagnosis and support cognitive and behavioral development.